The integrity of election organizers in the 2020 simultaneous regional head elections in Sekadau Regency - Hengki Hayatullah; Nur Hidayat Sardini (Universitas Islam Malang, 2022)
This research objective was to examine the integrity of the election organizers by analyzing the factors that led to the issuance of the Constitutional Court Decision Number: 12/PHP.BUP-XIX/2021 regarding the recount of the 2020 Simultaneous Regional Head elections in Sekadau Regency. It was known that the lawsuit resulting from the recapitulation of votes was filed by the pair Rupinus-Aloysius as the incumbent. The pair received 56,479 votes or 49.2 percent. Meanwhile, the rival pair Aron-Subandrio received 58,023 votes or 50.8 percent. This research used a descriptive qualitative method through a case study approach, which examined a